Integrated photonic polarizers with 2D reduced graphene oxide - Junkai Hu; Jiayang Wu; Di Jin; Wenbo Liu; Yuning Zhang; Yunyi Yang; Linnan Jia; Yijun Wang; Duan Huang; Baohua Jia; David J. Moss (Opto-Electronic Science)
Optical polarizers, which allow the transmission of specific polarization states, are essential components in modern optical systems. Here, we experimentally demonstrate integrated photonic polarizers incorporating reduced graphene oxide (rGO) films. 2D graphene oxide (GO) films are integrated onto silicon waveguides and microring resonators (MRRs) with precise control over their thicknesses and sizes, followed by GO reduction via two different methods including uniform thermal reduction and localized photothermal reduction. We measure devices with various lengths, thicknesses, and reduction degrees of GO films. The results show that the devices with rGO exhibit better performance than those with GO, achieving a polarization-dependent loss of ~47 dB and a polarization extinction ratio of ~16 dB for the hybrid waveguides and MRRs with rGO, respectively. By fitting the experimental results with theory, it is found that rGO exhibits more significant anisotropy in loss, with an anisotropy ratio over 4 times that of GO. In addition, rGO shows higher thermal stability and greater robustness to photothermal reduction than GO. These results highlight the strong potential of rGO films for implementing high-performance polarization selective devices in integrated photonic platforms.